A rare case of multiple benign tumors of gingiva in a 4 year old child. Issue 2 (August 2018) - Sethi, Pooja Ahluwalia; Jodhka, Sunaina; Sethi, Sumit; Kaur, Jasleen; Desai, Rajiv Surendra
Abstract: Hemangioma is a benign proliferation of blood vessels closely simulating normal vessels which may present at any age from birth to old age. Hemangiomas have a typical clinical pattern of rapid proliferation followed by involution, during which these may present with sudden increase in size raising suspicion of malignancy. However, they almost never turn malignant but occasionally may permeate all tissue barriers in an aggressive fashion. Infantile hemangioma is a form of benign vascular tumour presenting commonly in the head and neck region. This case report presents a very rare case of multiple benign lesions of infantile hemangioma in gingiva with a discussion of the relevant diagnostic and treatment modalities.